Impact of Graft Tunnel Placement on Short-Term Clinical Outcome Following Anterior Cruciate Ligament Reconstruction - Rogger M; Al-Dadah O (Malaysian Orthopaedic Journal)
Introduction: Anterior cruciate ligament (ACL) tears are a common musculoskeletal injury often requiring anterior cruciate ligament reconstruction (ACLR). Many factors are thought to influence patient outcome and determining the extent can allow for optimisation of patient care. One of these factors is graft tunnel placement, both femoral and tibial. The aim of this study was to investigate whether graft tunnel placement influences clinical outcome following ACLR. Materials and methods: The patient responses from six patient-reported outcome measures (PROM) at initial presentation and one year following ACLR, as well as demographic data at presentation, were collected. Graft tunnel placement was evaluated using 10 validated radiological measurements on antero-posterior and lateral radiographs following surgery. Results: A total of 45 patients were included in the study. There was a significant longitudinal improvement (p<0.001) for almost all PROM scores when comparing pre-operative to post-operative results. Overall, no significant correlation was demonstrated between graft tunnel placement and PROM scores, except for a weak association between femoral tunnel positioning on lateral view radiographs and the overall Knee injury and Osteoarthritis Outcome Score (rho=0.37, p=0.038) and the Lysholm score (rho=0.36, p=0.034) and also tibial tunnel placement on lateral view radiographs and the EQ-5D VAS score (rho=0.37, p=0.037). Conclusion: ACLR is a clinically successful treatment strategy for patients with symptomatic ACL tears. Graft tunnel positioning does not generally affect clinical outcomes, although there may be a weak association with femoral tunnel positioning on lateral radiographs.